2019
DOI: 10.3174/ajnr.a6157
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Spinal Cord Gray Matter Quantification: A Novel Approach

Abstract: BACKGROUND AND PURPOSE: Currently, accurate and reproducible spinal cord GM segmentation remains challenging and a noninvasive broadly accepted reference standard for spinal cord GM measurements is still a matter of ongoing discussion. Our aim was to assess the reproducibility and accuracy of cervical spinal cord GM and WM cross-sectional area measurements using averaged magnetization inversion recovery acquisitions images and a fully-automatic postprocessing segmentation algorithm. MATERIALS AND METHODS: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…With the approval of the first disease-modifying treatments for SMA, the need for biomarkers that allow reliable monitoring of the disease course and the therapeutic response in SMA patients has substantially grown. Current advances in morphometric MRI development allow gray (GM) and white matter (WM) quantification in the spinal cord (SC) ( 1 7 ), which may help in improving the in vivo characterization of motor neuron diseases or other neurodegenerative SC diseases. Imaging the cervical and lumbar enlargements could be informative, especially in lower motor neuron diseases, e.g., SMA, or lower motor neuron-predominant amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the approval of the first disease-modifying treatments for SMA, the need for biomarkers that allow reliable monitoring of the disease course and the therapeutic response in SMA patients has substantially grown. Current advances in morphometric MRI development allow gray (GM) and white matter (WM) quantification in the spinal cord (SC) ( 1 7 ), which may help in improving the in vivo characterization of motor neuron diseases or other neurodegenerative SC diseases. Imaging the cervical and lumbar enlargements could be informative, especially in lower motor neuron diseases, e.g., SMA, or lower motor neuron-predominant amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several semi-automated and automated tools ( 10 17 ) have been developed for segmentation of the SC GM and WM from MR images, including promising automated segmentation algorithms specifically developed for the AMIRA approach ( 7 , 14 ). The reliability of the segmentation methods in single center studies is in general high, and some methods have been validated in multi-centric settings ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Interestingly, DL algorithms based on CNNs were recently proposed for performing automated segmentation of upper cervical cord GM ( Paugam et al, 2019 , Tsagkas et al, 2019 ). Other studies applied AI on 1 H-MRS and identified N-acetylaspartate as the most significant metabolite differentiating between RRMS and SPMS (83% accuracy) ( Ek et al, 2020 ), although T2 LV and clinical history contributed as well (up to 87%) ( Ion-Margineanu et al, 2017 ).…”
Section: Clinical Applications Of Aimentioning
confidence: 99%
“…Spinal cord segmentation with the proposed open-source method outperformed the compared state-of-the-art method (DSC = 95% vs 88% of PropSeg ), while intramedullary MS lesion segmentation performance were comparable to manual segmentations. Other DL algorithms based on CNN were proposed for performing automated segmentation of upper cervical cord GM ( Paugam et al, 2019 , Tsagkas et al, 2019 ).…”
Section: Technical Applications Of Ai For Mri Acquisition and Analysismentioning
confidence: 99%
“…When Brucella invades the vertebral body or intervertebral disc tissue, it will cause spinal infection, called brucellar spondylitis (BS). Its incidence is also increasing year by year [ 5 ]. The use of medication alone for the treatment of BS is often unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%